Characterization of poly-hydroxybutyrate-hydroxyvalerate (PHB-HV)/corn starch blend films - Reis, Kelen Cristina dos (2007)
Blends of polyhydroxybutyrate-hydroxyvalerate (PHB-HV) with corn starch were prepared by solution casting from chloroform solutions at different compositions. The mechanical, thermal, morphological and physical-chemical properties were investigated using texture analyzer, differential scanning calorimetry, Fourier transform infrared spectrometry, X-ray diffractometry, optical microscopy, scanning electron microscopy and colorimetry. The Young´s Modulus, stress, strain and puncture decreased with increase in starch content in blend with PHB-HV. FTIR measurements indicated that no intermolecular interactions existed between the two polymers as no shift in the absorption peaks of the PHB-HV or starch in the blends was observed which suggests that PHB-HV and starch are immiscible. The blend showed low crystallinity (<4%). PHB-HV/ starch blends obtained by casting process were immiscible; however, the two components were completely miscible in the amorphous phase. Optical micrographs of PHB-HV/ starch blends films did not melt completely during blending. The blends showed a lack of interfacial adhesion between starch and PHB-HV and heterogeneous dispersion of starch granules over PHB-HV-rich matrix, as evidenced by SEM and optical micrographs of the surface. The colour difference and opacity showed small variation with increase of starch content.